Alkoxycarbonylation for fine chemicals: carbamates - Didgikar, M. R.; Joshi, S. S. (Industrial catalytic processes for fine and specialty chemicals, 2016)
Carbamates are an important class of compounds having wide applications in pharmaceutical, polymer, and agriculture industry. A brief account of the history of carbamates, their synthesis, and applications in chemical industry is presented in this chapter. A section on synthesis of carbamates by catalytic methoxycarbonylation of amines is also included. Results of lead-catalyzed methoxycarbonylation of aniline to methyl- N-phenyl carbamate are presented as a model case study. The synthesis of several carbamates has been reported using dimethyl carbonate to illustrate the usefulness of the method.